Improving key enzyme activities and quality of rice under various methods of zinc application - Mathpal, Bhupendra (Physiol Mol Biol Plants, 2015)
Zinc (Zn) is an important micronutrient for the physiology of plants. It is poorly available to the plants in soil solution. A pot experiment was conducted to evaluate effectiveness of various Zn application methods on key enzyme activities and protein content of two contrasting rice genotypes viz., PD16 (Zn efficient) and NDR359 (Zn inefficient). The treatments were, control (0 mg Zn kg(−1) soil), soil application (5 mg Zn kg(−1) soil), foliar application (0.5 % ZnSO(4) + 0.25 % lime at 30, 60 and 90 days after transplanting), soil (5 mg Zn kg(−1) soil) + foliar application of 0.5 % ZnSO(4) + 0.25 % lime at 30, 60 and 90 days after transplanting. Among all the methods tested soil+foliar application of Zn fertilizers was found most effective in increasing superoxide dismutase (SOD) and carbonic anhydrase (CA) activities as well as chlorophyll and protein content in both the rice varieties. NDR359, showed higher enzyme activities and more chlorophyll content in leaves than PD16, when Zn was applied either through foliar spray alone or in soil along with foliar application. Regarding the protein content in grains, PD16 showed higher protein content than NDR359, thus showed better translocation of Zn from leaves to grains.